Violência escolar: Uma perspectiva sobre o papel da biblioteca escolar - CORREA, Carlos Augusto Moreira (2019)
This work part of a school library perspective, in assisting the demands of an educational establishment, with the librarian professional ahead, with the freedom to develop their projects in partnership with the institution. Considering that the schools need to trace the profile of schoolchildren and their collaborators, in order to direct the educational applicability and the social relationship in the school environment, is part of the problem of how to help in the fight against school violence. Taking into account that managers and the school community understand the importance of the school library, the objective was to present the School Library as an aid to combat school violence, seeking to identify the main types of violence in the school environment; as well as presenting the school library as a space that helps in the pedagogical work to solve conflicts; and, finally, to propose alternatives for acting in addition to reading projects. In this way, a bibliographical survey was used as a methodology, posteriorly, as procedures, the data collection, characterizing this work as a qualitative and exploratory research. Therefore, it is observed that there is a lack of a tool to connect the dialogue between students and the pedagogical body of the educational institution, adding also the parents and responsible of the students. This allows to understand that the school library can and should assist in intellectual formation and is the ideal environment to assume this role / function.